Epidemiology and Clinical Outcomes Associated With Extensively Drug-Resistant (XDR) Acinetobacter in US Veterans' Affairs Health Care. (October 2020) - Fitzpatrick, Margaret; Suda, Katie; Poggensee, Linda; Vivo, Amanda; Gutkowski, Marissa; Wilson, Geneva; Evans, Charlesnika
Abstract : Background: Infections caused by Acinetobacter spp are often healthcare acquired, difficult to treat, and associated with high mortality. Extensively drug-resistant (XDR) Acinetobacter are nonsusceptible to at least 1 agent in all but 2 or fewer antimicrobial classes. Epidemiologic and outcome data for XDR Acinetobacter are limited and have largely been reported outside the United States. This national cohort study describes epidemiology, clinical characteristics, and outcomes for patients with XDR Acinetobacter in VA health care. Methods: This was a retrospective cohort study including microbiology and clinical data from all patients hospitalized between 2012 and 2018 at any VA medical center who had cultures that grew XDR Acinetobacter spp. Performance and reporting of bacterial speciation and antibiotic susceptibility testing were performed by each VA laboratory according to their protocol. Descriptive statistics were used to summarize data. Results: Of 11, 541 unique patients with 15, 358 cultures that grew Acinetobacter spp during the study period, 410 (3.6%) patients had 670 (4.4%) cultures that grew XDR Acinetobacter . Mean age was 68 years (SD, 12.2 years) and the median Charlson comorbidity index was 3 (IQR, 1–5). The greatest proportion of isolates were from the respiratory tract (n = 235, 35%) followed by urine (n = 184, 28%). The South had the greatest proportion of patients with XDR Acinetobacter (n = 162, 40%); almost all patients were seen at urban VA medical centers (n = 406, 99%). Most patients (n = 335, 82%) had had antibiotic exposure in the prior 90 days, most commonly vancomycin (n = 238, 65%) and third- or fourth-generation cephalosporins (n = 155, 38%). Most patients (n = 334, 81%) also had a hospital or long-term care admission in the prior 90 days. Fig. 1 shows antibiotic susceptibilities of XDR Acinetobacter isolates; polymyxins, tigecycline, and minocycline demonstrated the highest susceptibility. In-hospital mortality occurred in 90 patients (22%), 30-day mortality in 97 patients (24%), and 1-year mortality in 198 patients (48%). Of 93 patients, 23% were readmitted to the hospital within 90 days. Conclusions: Providers should maintain a heightened suspicion for infection with XDR Acinetobacter spp in older patients seen at urban medical centers who have had recent healthcare and antibiotic exposures, particularly if they have respiratory or urinary tract infections. Isolation of XDR Acinetobacter is associated with high in-hospital and 30-day mortality. New antibiotics targeting MDR gram-negative bacteria generally lack activity against Acinetobacter, leaving polymyxins, tigecycline, and minocycline as the only limited treatment options. Therefore, novel antibiotics for XDR Acinetobacter are urgently needed. Funding: None Disclosures: None